2022
DOI: 10.1186/s12909-022-03915-5
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous online lecturing or blended flipped classroom with jigsaw: an educational intervention during the Covid-19 pandemic

Abstract: Background The Covid-19 pandemic has changed the education system throughout the world. This study aimed to compare synchronous online lecturing with blended flipped classroom plus jigsaw in terms of their effects on the students’ learning, communication skills and critical thinking disposition. Methods This is an educational intervention conducted at the Nursing and Midwifery School of Shiraz University of Medical Sciences. Two incoming students o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…[ 40 ] verified that blended learning had a significant positive impact on university students’ critical thinking skills. [ 41 ] These studies showed that, compared to traditional methods of learning, blended learning was more effective in improving students’ critical thinking skills. The greater effectiveness of blended learning could be attributed to the fact that it allowed students to participate more in the learning process, as well as the fact that it possessed the benefits of both traditional learning and electronic learning, which enabled students to better analyze, interpret, and evaluate subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] verified that blended learning had a significant positive impact on university students’ critical thinking skills. [ 41 ] These studies showed that, compared to traditional methods of learning, blended learning was more effective in improving students’ critical thinking skills. The greater effectiveness of blended learning could be attributed to the fact that it allowed students to participate more in the learning process, as well as the fact that it possessed the benefits of both traditional learning and electronic learning, which enabled students to better analyze, interpret, and evaluate subjects.…”
Section: Discussionmentioning
confidence: 99%